2016
DOI: 10.3389/fpsyg.2016.00375
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Relationships of University Instructors’ Achievement Goals

Abstract: The present study examines the achievement goals of university instructors, particularly the structure of such goals, and their relationship to biographic characteristics, other aspects of instructors’ motivation, and teaching quality. Two hundred and fifty-one university instructors (184 without Ph.D., 97 with Ph.D., thereof 51 full professors; 146 males, 92 females) answered a questionnaire measuring achievement goals, self-efficacy, and enthusiasm in altogether 392 courses. Teaching quality was assessed usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 72 publications
(120 reference statements)
5
76
1
2
Order By: Relevance
“…Also, it can be assumed that the structure of achievement goals may be distinct for university instructors because they work in achievement settings that encompass a wide array of learning and performance aspects. For instance, concerning the defining elements of performance goals for different populations, for students, normative aspects (being better than others) of performance goals may be of particular importance, while for school teachers, appearing competent in front of students may be rather decisive; however, for university instructors, both aspects may constitute equal and distinct aspects of performance goals (Daumiller et al, 2016). Addressing these structural issues is important when investigating achievement goals in a new population and crucial in order to advance AGT.…”
Section: University Instructors' Achievement Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it can be assumed that the structure of achievement goals may be distinct for university instructors because they work in achievement settings that encompass a wide array of learning and performance aspects. For instance, concerning the defining elements of performance goals for different populations, for students, normative aspects (being better than others) of performance goals may be of particular importance, while for school teachers, appearing competent in front of students may be rather decisive; however, for university instructors, both aspects may constitute equal and distinct aspects of performance goals (Daumiller et al, 2016). Addressing these structural issues is important when investigating achievement goals in a new population and crucial in order to advance AGT.…”
Section: University Instructors' Achievement Goalsmentioning
confidence: 99%
“…Given this importance, in the next section we elaborate on existing findings concerning the structure of the achievement goals of university instructors. Daumiller et al (2016) found that splitting university instructors' performance goals into approach and avoidance components worked just as well as splitting them into appearance and normative components. All components yielded distinct relationships with other motivational variables and performance outcomes.…”
Section: University Instructors' Achievement Goalsmentioning
confidence: 99%
“…As both teaching and research constitute explicit achievement contexts, and achievement goals have been successfully used to describe the motivations for teaching at schools and universities (Butler, 2007;Daumiller, Dickhäuser, & Dresel, 2019;Daumiller, Dickhäuser, Grassinger, & Dresel, 2016;Retelsdorf, Butler, Streblow, & Schiefele, 2010) as well as for university scholars' vocational goal striving on a general level (without distinguishing between teaching, research, and other activities; Janke & Dickhäuser, 2018), we applied Achievement Goal Theory (AGT) as a framework to describe motivations for research. As AGT has not yet been investigated in university researchers with respect to their research activities, an important prerequisite is to confirm the suitability of this approach.…”
Section: Burnout/engagement and Professional Learningmentioning
confidence: 99%
“…B. besser als andere zu sein; Normziele) oder auf der Erscheinung liegt (z. B. einen guten Eindruck machen, unabhängig davon, wie kompetent man tatsächlich ist; Erscheinungsziele)denn diese unterschiedlichen Aspekte können differenziell mit unterschiedlichem Erleben und Verhalten assoziiert sein Daumiller, Grassinger, Dickhäuser & Dresel, 2016;s. a. Hulleman et al, 2010;Senko & Dawson, 2017).…”
Section: Struktur Der Zieleunclassified